Influencia del tamaño de muestra en el volumen y valoración económica referencial promedio en especies comerciales de un bosque natural de colina baja, Loreto, Perú – 2023 - Perez Pinedo, Daniel (2025)
The objective of the study was to determine if there is an influence on the timber volume and economic valuation of commercial species in a low hill forest of the Oroza basin by sample size. Five samples were used for the evaluation, Sample 1 (M1) with 23,33 ha; Sample 2 (M2) with 46,66 ha; Sample 3 (M3) with 69,99 ha. Sample 4 (M4) with 93,32 and Sample 5 (M5) with 116,65 ha. The results of the research were, for the volume of wood in the M1= 7.04 m3/ha; M2= 7,73 m3/ha; M3= 6,90 m3/ha; M4= 6,03 m3/ha and M5= 5,25 m3/ha; average = 6,6, m3/ha; The results were also diverse, in M1= S/ 1 011,3 soles; M2= S/ 1 046,8 soles; M3= S/ 913,7 soles; M4= S/ 819,9 soles and M5= S/ 707,0 soles; the average was S/ 718,6 soles. In conclusion, sample 2 has been considered as representative for the low hill forest.